Effect of self-employment on the sub-health status and chronic disease of rural migrants in China - Jian Zhou; Qiushi Wu; Zicheng Wang (BMC, 2021)
Abstract Background Rural migrants usually suffer from major disease risks, but little attention had been paid toward the relationship between self-employment behavior and health status of rural migrants in China. Present study aims to explore the causal effect of self-employment behavior on rural migrants' sub-health status and chronic disease. Two research questions are addressed: does self-employment status affect the sub-health status and chronic disease of rural migrants? What is potential mechanism that links self-employment behavior and health status among rural migrants in China? Methods The dataset from the 2017 National Migrants Population Dynamic Monitoring Survey (NMPDMS-2017) was used to explore the causal effect. Logit regression was performed for the baseline estimation, and linear probability model with instrument variable estimation (IV-LPM) was applied to correct the endogeneity of self-employment. Additionally, logit regression was conducted to explore the transmission channel. Results Self-employed migrants were more susceptible to sub-health status and chronic disease, even when correcting for endogeneity. Moreover, self-employed migrants were less likely to enroll in social health insurance than their wage-employed counterparts in urban destinations. Conclusion Self-employed migrants were more likely to suffer from sub-health status and chronic disease; thus, their self-employment behavior exerted a harmful effect on rural migrants' health. Social health insurance may serve as a transmission channel linking self-employment and rural migrants' health status. That is, self-employed migrants were less prone to participate in an urban health insurance program, a situation which leaded to insufficient health service to maintain health.